2020
DOI: 10.7150/ijbs.39895
|View full text |Cite
|
Sign up to set email alerts
|

Circ-100290 Positively Regulates Angiogenesis Induced by Conditioned Medium of Human Amnion-Derived Mesenchymal Stem Cells Through miR-449a/eNOS and miR-449a/VEGFA Axes

Abstract: The powerful pro-angiogenic capacity of human amnion-derived mesenchymal stem cells (hAMSCs) could be a valuable therapeutic angiogenesis strategy for bone regeneration. However, the molecular mechanisms underlying this process remain largely unknown. Herein, we report upregulated expression of circular RNA 100290 (circ-100290) and an enhanced angiogenic phenotype of human umbilical vein endothelial cells (HUVECs) incubated with conditioned medium from hAMSCs (hAMSC-CM), whereas downregulation of circ-100290 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Studies showed that hAMSCs promoted angiogenesis by regulating the ERK1/2-MAPK signaling pathway [ 13 ] and that knockdown of lnRNA H19 significantly inhibited the angiogenic function of hAMSCs, in which the mechanism might be related to EZH2 degradation and VASH1 activation [ 67 ]. In addition, Tang et al demonstrated that the angiogenesis of hAMSCs might be related to inhibit the functions of the Circ-ABCB10/miR-29b-3p/VEGFR, Circ-100290/miR-449a/eNOS, and Circ-100290/miR-449a/VEGFA axes in human umbilical vein endothelial cells [ 68 , 69 ]. Taken together, although the underlying mechanism of hAMSCs in angiogenesis is not fully elucidated the cells may become a useful reagent in various vascular diseases.…”
Section: Characteristics Of Human Amnion-derived Stem Cellsmentioning
confidence: 99%
“…Studies showed that hAMSCs promoted angiogenesis by regulating the ERK1/2-MAPK signaling pathway [ 13 ] and that knockdown of lnRNA H19 significantly inhibited the angiogenic function of hAMSCs, in which the mechanism might be related to EZH2 degradation and VASH1 activation [ 67 ]. In addition, Tang et al demonstrated that the angiogenesis of hAMSCs might be related to inhibit the functions of the Circ-ABCB10/miR-29b-3p/VEGFR, Circ-100290/miR-449a/eNOS, and Circ-100290/miR-449a/VEGFA axes in human umbilical vein endothelial cells [ 68 , 69 ]. Taken together, although the underlying mechanism of hAMSCs in angiogenesis is not fully elucidated the cells may become a useful reagent in various vascular diseases.…”
Section: Characteristics Of Human Amnion-derived Stem Cellsmentioning
confidence: 99%
“…Kang et al [ 26 ] found that adipose-derived stem cells induced angiogenesis through microvesicle transport of miRNA-31. Moreover, circRNA 100290 was reported to positively regulate angiogenesis induced by a conditioned medium of human amnion-derived MSCs through miR-449a/eNOS and miR-449a/VEGFA axes [ 27 ]. Previous studies have shown that circRNAs can function as miRNA sponges to competitively bind to miRNA, thus abrogating the inhibitory effect of miRNA on target genes [ 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, circRNA 100290 was reported to positively regulate angiogenesis induced by a conditioned medium of human amnion-derived MSCs through miR-449a/eNOS and miR-449a/VEGFA axes [26] . Our data showed that miR-29b-1-5p, which was downregulated in WJ-MSCs during coculture with damaged ESCs, directly target 3 -UTR of RAP1B.…”
Section: Discussionmentioning
confidence: 99%